More or less dead: feminicide, haunting, and the ethics of representation in Mexico - Driver, Alice (The University of Arizona Press, 2015)
Through interviews with filmmakers, photographers, artists, and writers, this book analyzes how victims of gender violence have been represented in the mainstream media and how a number of writers, filmmakers, and artists work against this trope to humanize the victims of these crimes. (Provided by publisher)